2015
DOI: 10.1515/joim-2015-0024
|View full text |Cite
|
Sign up to set email alerts
|

The “Retro” Trend in Marketing Communication Strategy of Global Brands

Abstract: The main objective of this article is to present the relevance and possibilities of using the “retro” trend in marketing communication strategy of global brands, taking into account intercultural environment of companies. In the article the examples of retro-communication of global brands are presented. The results of comparative studies of attitudes of French and Polish consumers concerning retro communication campaigns of global brands are also analysed, taking into account the product category, as well as g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…Past research showed that integrating past codes and symbols into existing products reinforces the personal identity of a consumer anchored in his roots (Maffesoli, 2003). Such integration is reassuring as it acts as a stable point, an emotional pillar, a founder or a comforting expectation (Grębosz and Pointet, 2015). In keeping with the self-continuity theory, these pastthemed codes and symbols are reassuring in that they contribute to the self-enhancement and self-protection motives of consumers (Sedikides and Alicke, 2012).…”
Section: Song Set Listmentioning
confidence: 83%
See 2 more Smart Citations
“…Past research showed that integrating past codes and symbols into existing products reinforces the personal identity of a consumer anchored in his roots (Maffesoli, 2003). Such integration is reassuring as it acts as a stable point, an emotional pillar, a founder or a comforting expectation (Grębosz and Pointet, 2015). In keeping with the self-continuity theory, these pastthemed codes and symbols are reassuring in that they contribute to the self-enhancement and self-protection motives of consumers (Sedikides and Alicke, 2012).…”
Section: Song Set Listmentioning
confidence: 83%
“…Consumers' insecurity, which is a generalized sense of uncertainty, vulnerability and fear, may therefore result in consumers' positive attitudes toward retro brands (Zhou et al, 2013). Products and brands that share references to the past may have helped create a reassuring effect through their tangible connection to the past and provide positive nostalgic feelings (Grębosz and Pointet, 2015).…”
Section: Conceptual Backgroundmentioning
confidence: 99%
See 1 more Smart Citation
“…Consumers are said to search for the brands that deliver additional value connected with feeling of security and calm (Grebosz, Pointet, 2015). Likewise, Ling Zhou et al (2013) noticed that existential insecurity and social insecurity enhanced consumers' preference for nostalgic products.…”
Section: Revealing Retro Consumers In the Retail Environmentmentioning
confidence: 99%
“…In global communication; they highlight the characteristics, history and eternal values of the brand. Because of these situations; Retro marketing is to focus on goals to improve brand value and strengthen brand image 10 . Sports marketing is one of the areas that applies retro the most.…”
Section: Introductionmentioning
confidence: 99%